2012
DOI: 10.1055/s-0031-1298605
|View full text |Cite
|
Sign up to set email alerts
|

Cervical artificial disc replacement versus fusion in the cervical spine: a systematic review comparing multilevel versus single-level surgery

Abstract: Study design: Systematic review.Clinical questions: What is the effectiveness of multilevel cervical artificial disc replacement (C-ADR) compared with multilevel fusion with respect to pain and functional outcomes, and are the two procedures comparable in terms of safety? What is the effectiveness of multilevel C-ADR compared with single-level C-ADR with respect to pain and functional outcomes, and are the two procedures comparable in terms of safety?Methods: A systematic review was undertaken for articles pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
(23 reference statements)
1
16
0
Order By: Relevance
“…
C erviCal total disc replacement (cTDR) in properly indicated patients with single-level cervical disc pathology has been demonstrated to achieve satisfactory neural decompression and clinical outcomes equivalent to or better 4,6,7,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]38 than anterior cervical discectomy and fusion (ACDF) in 7 different prospective, randomized, controlled US FDA trials. Single-level longterm data have been published on the Bryan disc, 34 ProDisc-C, 41 and Prestige ST disc, 8 but this is the first report on the 5-year investigational device exemption (IDE) data for 2-level cervical arthroplasty.

Although both ACDF and cTDR satisfactorily treat clinically symptomatic cervical pathology, arthrodesis alters cervical mechanics 1,2,11 by placing increased stresses on ad- obJective The purpose of this study was to report the outcome of a study of 2-level cervical total disc replacement (Mobi-C) versus anterior cervical discectomy and fusion (ACDF).

…”
mentioning
confidence: 99%
“…
C erviCal total disc replacement (cTDR) in properly indicated patients with single-level cervical disc pathology has been demonstrated to achieve satisfactory neural decompression and clinical outcomes equivalent to or better 4,6,7,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]38 than anterior cervical discectomy and fusion (ACDF) in 7 different prospective, randomized, controlled US FDA trials. Single-level longterm data have been published on the Bryan disc, 34 ProDisc-C, 41 and Prestige ST disc, 8 but this is the first report on the 5-year investigational device exemption (IDE) data for 2-level cervical arthroplasty.

Although both ACDF and cTDR satisfactorily treat clinically symptomatic cervical pathology, arthrodesis alters cervical mechanics 1,2,11 by placing increased stresses on ad- obJective The purpose of this study was to report the outcome of a study of 2-level cervical total disc replacement (Mobi-C) versus anterior cervical discectomy and fusion (ACDF).

…”
mentioning
confidence: 99%
“…Despite a plethora of systematic reviews on cervical disc replacement, only a few studies assess publication bias directly [20][21][22][23][24][25][26][27][28][29][30][31]. There are several studies that have demonstrated a publication bias in the cervical disc replacement literature [32,33].…”
Section: Publication Biasmentioning
confidence: 99%
“…These studies are prospective multicenter trials, in which patients were randomized to undergo arthroplasty or fusion surgery, and success is defined as a composite score based on validated clinical scales. Previous reviews have thoroughly documented these trials and related studies (14)(15)(16) .…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Subsequent studies have demonstrated equivalent or superior clinical outcomes when comparing single level to multilevel CA (46)(47)(48) . In comparison to ACDF, there is evidence to suggest that CA demonstrates improved clinical outcomes; although there are few studies available that evaluate this issue (16,23,49) . The Mobi-C Cervical Disc is currently the only FDA-approved device for one or twolevel disc replacement, and has been demonstrated to maintain effectiveness at 2 and 4 years following implantation (23,50) .…”
Section: Multi-level Diseasementioning
confidence: 99%